Macrofauna-sized foraminifera in epibenthic sledge samples from five areas in the eastern Clarion-Clipperton Zone (equatorial Pacific) - Gooday, Andrew J.; Wawrzyniak-Wydrowska, Brygida (Frontiers in Marine Science, 2023)
Benthic foraminifera cannot be sampled adequately using a single device. Smaller taxa are best collected using multicorers, the larger with box corers, but towed devices (dredges, trawls and epibenthic sledges) also retain many larger species. Here, we describe macrofaunal (>300 µm) foraminiferal assemblages obtained using an epibenthic sledge (EBS) in the Clarion-Clipperton Zone (eastern equatorial Pacific), a region hosting seafloor deposits of polymetallic nodules. Twelve EBS samples were collected in four areas licenced for exploration by the International Seabed Authority (ISA) to German, IOM, Belgium and French contractors, and to APEI-3, one of the protected Areas of Special Scientific Interest designated by the ISA. We recognised 280 morphospecies among 1954 specimens, with between 74 (IOM) and 121 (Belgium) in particular areas. Most (92.7%) were single-chambered monothalamids, of which 75 species (26.8%) belonged to the Komokioidea (‘komoki’), 47 (16.8%) to branched and unbranched tubes, 33 (11.8%) to chain-like and 32 (11.4%) to various ‘komoki-like’ forms. Fragments of megafaunal xenophyophores represented 21 species (7.50%), including Spiculammina delicata, previously reported only from the Russian area. Rarefaction curves and sample coverage completeness curves suggest that only a fraction of the macrofaunal foraminiferal diversity had been sampled. The occurrence of 71.8% of species in 1-2 of the 12 samples and 84.9% in 1-3 of the samples was a likely result of substantial undersampling. Dissimilarity in species composition between areas was very high: 64.2% (German vs IOM area) to 86.9% (German area vs APEI-3). Similarity within a single area was quite low: 29.1% (German) to 45.1% (IOM). In multidimensional scaling (MDS) plots, the APEI-3 area was clearly distinct in terms of faunal composition from all other areas, the French area somewhat separated from the German, IOM and Belgium areas, with the German and IOM samples being the most similar. These patterns may reflect the geographical separation of the French and APEI-3 areas and their location in deeper, more oligotrophic waters. Our study demonstrates that EBS samples from the eastern CCZ are a rich source of novel foraminiferal taxa, particularly light, easily resuspended komoki, providing a valuable perspective on foraminiferal biodiversity.